ANALISIS SIA SIKLUS PENJUALAN PADA PT. ENSEVAL PUTERA MEGATRADING TBK SURABAYA - Sholichah, Ninik; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTA good companies will have various competitive advantages when they have good information system, so theywill be able to compete with other companies. This research is meant to analyze the sales cycle of accountinginformation system at PT. Enseval Putera Megatrading, Tbk Surabaya. The research has been done by seeing theimpact and the internal control in the company. This research has been carried out by using qualitative methodin which the qualitative research has been conducted in natural condition and inventive. The technique has beencarried out by using interview technique in which the interview is the verification of the information which hasbeen obtained before. The result of this research shows that the impact of accounting information system on salescycle is quite effective. The internal control system which has been implemented by the company is considered tobe firm. It has been found that the existence of internal control which has been implemented by the company inthe procedure of sales system can minimize the existing risk.Keywords: Accounting Information System, Sales, Control.